2000
DOI: 10.1177/204748730000700302
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Studies on Myocardial Stretch and Ventricular Arrhythmia in Hypertrophied and Non-Hypertrophied Hearts

Abstract: Hypertension affects about 5% of western populations and in the majority of cases it is of unknown aetiology. It exposes the heart to greater levels of myocardial stretch as a result of increased systolic pressure and peripheral resistance. Under certain circumstances myocardial stretch may trigger arrhythmias but the mechanisms and clinical importance of this phenomenon are unclear. This article outlines the risks of sudden cardiac death conferred by hypertension and left ventricular hypertrophy, presents the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…In addition to autonomic responses, this temporal pattern can be attributed to differences in the substrate, created by ischemia versus evolving MI ( 1 , 25 ). Furthermore, LV-afterload reduction [often observed as a delayed effect after clonidine administration ( 38 )] may have contributed to this pattern, by decreasing wall-stress and, thereby, stretch-induced VT/VF ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to autonomic responses, this temporal pattern can be attributed to differences in the substrate, created by ischemia versus evolving MI ( 1 , 25 ). Furthermore, LV-afterload reduction [often observed as a delayed effect after clonidine administration ( 38 )] may have contributed to this pattern, by decreasing wall-stress and, thereby, stretch-induced VT/VF ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…The role that this plays in healthy heart is unclear, but we hypothesised that an exaggeration of this response in hypertrophic hearts may explain the high risk of SCD in patients with hypertrophy and early failure. The hypertrophied heart indeed shows increased sensitivity to stretch-induced arrhythmias2 and increased stretch-activated currents in myocytes from hypertrophied animal and human hearts has been directly demonstrated 3. We have now extended these observations by examining stretch-induced ectopic beats in isolated hearts from Wistar-Kyoto (control) and SHR 4.…”
mentioning
confidence: 66%
“…Cheng et al (1995) found an increase in programmed cell death in response to myocardial distension [51]. In this case, stretching of the myocardium can occur both in physiological conditions (for example, heavy physical exertion) and in several pathological conditions (for example, in heart failure and arterial hypertension), which possibly contributes to an increase in the level of troponins [52][53][54]. Singh et al (2001) investigated the effect of enhanced neurohumoral stimulation on apoptosis processes and found that stimulation of beta1-adrenergic receptors induces apoptosis via activation of adenylyl cyclase [55], while stimulation of beta2-adrenergic receptors, on the contrary, has an antiapoptotic effect [56,57].…”
Section: The Role Of Apoptosis In the Release Of Troponins From Cardiomyocytesmentioning
confidence: 99%